1981
DOI: 10.1149/1.2127637
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of CVD Silicon with Molybdenum Substrates

Abstract: unless CC License in place (see abstract). ecsdl.org/site/terms_use address. Redistribution subject to ECS terms of use (see 129.100.58.76 Downloaded on 2015-04-12 to IP ) unless CC License in place (see abstract). ecsdl.org/site/terms_use address. Redistribution subject to ECS terms of use (see 129.100.58.76 Downloaded on 2015-04-12 to IP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

1981
1981
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 6 publications
0
3
1
Order By: Relevance
“…The phase diagram of Mo–Si confirms that all three phases are possible to evolve at temperatures around 1200 °C. The study of Yoon et al provides evidence that silicon is not able to adhere over longer annealing times to the Mo–silicide phases due to the large mismatch of the CTE (Si: 3.8 × 10 −6 K −1 , MoSi 2 : 9.5 × 10 −6 K −1 ) . In contrast to the scenario under vacuum described earlier, under oxygen containing atmosphere such as lab air the silicon coating on the TZM substrate behaves differently in the current study.…”
Section: Discussioncontrasting
confidence: 63%
“…The phase diagram of Mo–Si confirms that all three phases are possible to evolve at temperatures around 1200 °C. The study of Yoon et al provides evidence that silicon is not able to adhere over longer annealing times to the Mo–silicide phases due to the large mismatch of the CTE (Si: 3.8 × 10 −6 K −1 , MoSi 2 : 9.5 × 10 −6 K −1 ) . In contrast to the scenario under vacuum described earlier, under oxygen containing atmosphere such as lab air the silicon coating on the TZM substrate behaves differently in the current study.…”
Section: Discussioncontrasting
confidence: 63%
“…Solid-state diffusion-controlled process.-Generally, the treating temperatures for formation of MoSi 2 coating by pack siliconizing or CVD are considered to be very high ͑Ͼ900°C͒, so it is commonly accepted that at such high temperatures the rate-limiting step for growth of MoSi 2 coating is a solid-state diffusion process of Si through MoSi 2 coating from the surface to the interface of MoSi 2 /Mo rather than a chemical reaction process of Si with Mo to form MoSi 2 phase. [31][32][33] It is well known that Si nonstoichiometry in MoSi 2 phase is below about 0.2 atom %, 34 and thus the diffusivity of Si through MoSi 2 phase was independent of composition, which is reasonable for diffusion in a line compound, and the dominant diffusion element in the MoSi 2 phase is Si. 19,31,32,35 From Fick's first law, the Si flux (J Si s ) consumed by the solid-state diffusion process of Si from the surface of the MoSi 2 coating to the MoSi 2 /Mo interface is given by…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…[31][32][33] It is well known that Si nonstoichiometry in MoSi 2 phase is below about 0.2 atom %, 34 and thus the diffusivity of Si through MoSi 2 phase was independent of composition, which is reasonable for diffusion in a line compound, and the dominant diffusion element in the MoSi 2 phase is Si. 19,31,32,35 From Fick's first law, the Si flux (J Si s ) consumed by the solid-state diffusion process of Si from the surface of the MoSi 2 coating to the MoSi 2 /Mo interface is given by…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…During the diffusion processes, the supersaturation of lattice vacancies develops into an interior pore which becomes the inner part of the final hollow structure. This strategy has been extensively used for noble and transition metals, metal oxides, and sulfides. ,, However, the Kirkendall effect for Si or Ge has been rarely investigated because their diffusivities were expected not as high as the Kirkendall effect induced. Although a few trials for Kirkendall effect of Si or Ge were reported, they found the Kirkendall effect mostly in only thin film structure, and the mechanism of the effect for such elements has remained elusive. Especially, the Kirkendall effect of Si element has not been apparent hitherto.…”
mentioning
confidence: 99%